Doktrin ekonomi Islam - Afzlalur Rahman (Dana Bhakti Wakaf, 1995)
Oen, Jil. 2=c.1-5; Jil. 3=c.1-2; Jil.4=c.1/tr, Jil. 1=c.1/ast jil.1 -c.2/jil.1=c.3/tr, jil.1=c.4-5; jil.4=c.2/ tr, jil. 2=c.6/why, jil.3,=c.3-4